Multi-sphere coupling characteristics and gas-bearing controlling factors of calcareous shale reservoirs in the Yadu-Ziyun-Luodian Aulacogen under Early Carboniferous platform-basin transitional sedimentary system, South China - Yuan, Kun; Feng, Bing; Li, Gangquan; Xue, Zongan; Lin, Tuo; Fang, Xinxin; Sun, Xiangcan; Xu, Yinbo; Zheng, Fengzan (Frontiers in Earth Science, 2025)
The Early Carboniferous Dawuba Formation within the Yadu-Ziyun-Luodian aulacogen (YZLA), southern China, represents a significant shale gas play formed within a dynamic platform-basin transitional sedimentary system influenced by multi-sphere coupling (the dynamic interaction of tectonic, climatic, and oceanic spheres). This setting generated pronounced heterogeneities in lithology and gas content. Integrating field geological surveys and well data, this study comprehensively evaluates the mineralogy, geochemistry, structural features, and gas content of these shales to decipher the key factors controlling gas enrichment, particularly in this tectonically complex area. A crucial finding is the distinction between low-energy, “thick-bedded” deposits and higher-energy, “thin interbedded” sections characterized by frequent alternations of mudstone and argillaceous limestone (0.5–5 m single layers, mudstone:limestone ratio 1:1–1:2). Significantly, these thin interbedded sections demonstrate superior reservoir quality, exhibiting higher porosity (∼2.9%) and notably higher gas content (∼2.5 m3/t). We reveal that in the YZLA’s complex structural setting, shale gas content is primarily governed by preservation conditions dictated by the unique litho-mechanical properties of the interbedded strata, rather than traditional controlling factors like TOC abundance or matrix porosity. The frequent interlayering promotes stable micro-fractures, supported by clay-rich horizons and effectively sealed by compact limestone, thereby enhancing secondary storage capacity and permeability for free gas. Consequently, these thin interbedded sections represent the most favorable intervals for shale gas accumulation, identifying them as the prime targets for achieving Early Carboniferous shale gas breakthroughs in the YZLA.